Effects of plyometric training volume and training surface on explosive strength - Ramirez-Campillo, R.; Andrade, D. C.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study is to examine the effects of different volume and training surfaces during a short-term plyometric training program on neuromuscular performance. Twenty-nine subjects were randomly assigned to 4 groups: control group (CG, n = 5), moderate volume group (MVG, n = 9, 780 jumps), moderate volume hard surface group (MVGHS, n = 8, 780 jumps), and high volume group (HVG, n = 7, 1,560 jumps). A series of tests were performed by the subjects before and after 7 weeks of plyometric training. These tests were measurement of maximum strength (5 maximum repetitions [5RMs]), drop jumps (DJs) of varying heights (20, 40, and 60 cm), squat and countermovement jumps (SJ and CMJ, respectively), timed 20-m sprint, agility, body weight, and height. The results of the present study suggest that high training volume leads to a significant increase in explosive performance that requires fast stretch-shortening cycle (SSC) actions (such as DJ and sprint) in comparison to what is observed after a moderate training volume regimen. Second, when plyometric training is performed on a hard training surface (high-impact reaction force), a moderate training volume induces optimal stimulus to increase explosive performance requiring fast SSC actions (e.g., DJ), maximal dynamic strength enhancement, and higher training efficiency. Thus, a finding of interest in the study was that after 7 weeks of plyometric training, performance enhancement in maximal strength and in actions requiring fast SSC (such as DJ and sprint) were dependent on the volume of training and the surface on which it was performed. This must be taken into account when using plyometric training on different surfaces.